On Rayleigh waves in a piezoelectric semiconductor thin film over an elastic half-space. (15th August 2021) - Tian, Ru; Nie, Guoquan; Liu, Jinxi; Pan, Ernian; Wang, Yuesheng
Highlights: The semiconductor property is considered to study the propagation of Rayleigh waves. The semiconductor property has obvious effect on the propagation behavior. The Rayleigh waves can propagate with a wave speed that is larger than csh . The 2nd dispersion curve could be discontinuous due to the zero imaginary wave speed. The propagation of Rayleigh wave can be manipulated by applying bias electric filed. Abstract: Some piezoelectric materials, such as zinc oxide (ZnO), have not only piezoelectric property but also semiconductor characteristics. However, the semiconductor characteristics are omitted in the study of elastic surface waves propagation in the surface acoustic waves devices that composed of these materials with elastic materials. In this paper, analytical solutions for the Rayleigh waves in a piezoelectric semiconductor (PSC) thin film perfectly bonded to an elastic half-space are obtained. The general solution of each layer is derived by using wave-mode method. Making use of the boundary conditions on the top of the thin film and the interface conditions between the thin film and the half-space, the dispersion relations are given analytically. Numerical examples show the dispersion and attenuation curves of the Rayleigh waves in the ZnO PSC thin film/diamond elastic half-space with fixed thin-film thickness, steady-state carrier density and biasing electric field. Notably, the Rayleigh waves can propagate with a wave speed larger than the shear-wave speed in the elastic half-space, which is quite different from that in the corresponding elastic half-space covered with a piezoelectric thin film or elastic thin film. We then investigate the effect of steady-state carrier density, thin-film thickness, and biasing electric field on the maximum speed of the Rayleigh waves and the interaction of the first two modes in the ZnO PSC thin film/diamond elastic half-space, which could be very helpful as theoretical guidance for the design of the PSC surface acoustic wave devices. Graphical abstract: Image, graphical abstract